Salt freezing resistance improvement of cement-based materials incorporated with calcined layered double hydroxide - Jinyang Huo; Tonghuan Zhang; Zhenjun Wang; Xiaofeng Wang; Xin Ji; Pei Wang (Journal of Traffic and Transportation Engineering (English ed. Online), 2023)
Salt freezing damage has severe impacts on durability of cement-based materials (CBMs). Calcined layered double hydroxide (CLDH), as an efficient environmental-friendly adsorption material, can impart excellent salt freezing resistance to CBMs. In this work, salt freezing resistance improvement of CBMs incorporated with CLDH was experimentally evaluated by chloride binding capacity, mass loss rate, relative dynamic elastic modulus, setting time, compressive strength, and micro structure tests. Beside these, the salt freezing damage model was established to effectively express the quantitative relationship between influencing factors and evaluation indexes of the salt freezing resistance of CBMs. Results show that CLDH can reconstruct its original layered structure to form reconstructed layered double hydroxide (RLDH). RLDH combines with chloride ions to form RLDH-Cl recrystallization, which can improve chloride binding capacity and pore structures of CBMs to relieve the salt freezing damage. The salt freezing damage model indicates that the suitable CLDH content can evidently alleviate the salt freezing damage, which facilitates the quantitative analysis of the effect of CLDH on the salt freezing resistance of CBMs.